Enhanced repair of meniscal hoop structure injuries using an aligned electrospun nanofibrous scaffold combined with a mesenchymal stem cell-derived tissue engineered construct. (February 2019) - Shimomura, Kazunori; Rothrauff, Benjamin B.; Hart, David A.; Hamamoto, Shuichi; Kobayashi, Masato; Yoshikawa, Hideki; Tuan, Rocky S.; Nakamura, Norimasa
Abstract: Damage to the meniscal hoop structure results in loss of biomechanical function, which potentially leads to the extrusion of the meniscus from the weight bearing area. However, there have been no established, effective treatments for such injuries. The purpose of this study was to investigate the applicability of cell-seeded nanofibrous scaffolds to repair the damaged meniscal hoop structure along with the prevention of subsequent cartilage degeneration using a rabbit model. Meniscal radial defects (5 mm width) in the medial meniscus were treated by wrapping and suturing with either an aligned electrospun nanofibrous scaffold alone or a scaffold combined with a tissue engineered construct (TEC) derived from synovial mesenchymal stem cells (MSCs), with the scaffold fiber direction matching that of the meniscal circumferential fibers. The MSC-based TEC-combined nanofibrous scaffolds contributed significantly to the prevention of meniscal extrusion and exerted a chondroprotective effect, compared with either scaffold alone or the untreated control groups. Also, meniscal defects treated with such TEC-combined nanofibrous scaffolds were consistently repaired with a fibrocartilaginous tissue. In this study, we have demonstrated the feasibility of a combined TEC-nanofibrous scaffold to repair the meniscal hoop structure, and prevent the progression to cartilage degeneration, as a potential tissue engineering method.